Medicinal Properties of Honey and Cordyceps Mushrooms - Theodor-Ioan Badea; Emanuel Vamanu (Nutraceuticals, 2023)
In a world still recovering after the COVID-19 pandemic, the consequences of which are still not entirely known, the attention of scientists worldwide is drawn to natural products with positive effects on immunity. The starting point for tackling such a subject is proper documentation of substances used in traditional medicine, which usually have significant nutritional and functional values. Among the most well-known of these substances are mushrooms and honey, both of which have been used for thousands of years all around the globe. The following work aims to gather information about the properties of honey and Cordyceps sp. mushrooms by studying the scientific literature available at this point. With the proper use of this information, it will be possible to develop products that incorporate the studied ingredients to increase their functional and medicinal value.